Analisis Pengaruh Tingkat Pendidikan dan Upah Terhadap Produktifitas Kerja Pegawai Dinas Pasar Kota Padang - Yuli Angraini (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
This study is to test and analysis education influence and wages toproductivity work employee office Dinas Pasar Kota Padang. Independent variable used independently is education influence (X1) and wages (X2), variable dependentis productivity work employee (Y). Breedstudy methodused is causative method. Data Used is data primer and sekunder. Data Primer obtained with method interview to sample as much ninety seventh people employee Dinas Pasar Kota Padang. As for instrument analysis which is Regresion Linear Multiple with Programe SPSS version 19.0.